Perubahan Psikologis Pada Ibu Hamil Trimester III - R. Nety Rustikayanti; Ira Kartika; Yanti Herawati (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2016)
A woman on the gestation period will experience both physical and psychological changes. These changes have an impact on the fulfillment of basic needs, including sexuality. Changes in pregnant women’s perceived psychology can result in decreased sexual desire of the women. This study aimed to describe the relationship of psychological changes of pregnant women with the husband’s sexual satisfaction level. The study used cross sectional design with a population of third trimester pregnant women who did checkups in May 2015 as many as 183 couples. Sampling technique used accidental sampling and sample size was 46 couples. The instrument used was a questionnaire and Psychological Changes Index of Sexual Satisfaction (ISS). Data analysis used Chi-square test. The results showed that as many as 54.3% of respondents experienced a positive psychological change. Conclusion of the study is that the more positive physiological changes in pregnant women will result in higher sexual satisfaction of her husband.